2022
DOI: 10.3390/jox12030017
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methods for Removal of Ceftriaxone from Wastewater

Abstract: The presence of pharmaceuticals in surface water and wastewater poses a threat to public health and has significant effects on the ecosystem. Since most wastewater treatment plants are ineffective at removing molecules efficiently, some pharmaceuticals enter aquatic ecosystems, thus creating issues such as antibiotic resistance and toxicity. This review summarizes the methods used for the removal of ceftriaxone antibiotics from aquatic environments. Ceftriaxone is one of the most commonly prescribed antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 128 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Ceftriaxone has a low potential for bioaccumulation [ 42 ]; nevertheless, it is eliminated unaltered in the urine (by glomerular filtration) and bile. Even though ceftriaxone is one of the most prescribed antibiotics in health facilities, there is little information regarding its occurrence in the environment [ 43 ]. A recent study in India found high levels of ceftriaxone (from 1.25 to 29.15 µg/mL) in hospital effluent [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone has a low potential for bioaccumulation [ 42 ]; nevertheless, it is eliminated unaltered in the urine (by glomerular filtration) and bile. Even though ceftriaxone is one of the most prescribed antibiotics in health facilities, there is little information regarding its occurrence in the environment [ 43 ]. A recent study in India found high levels of ceftriaxone (from 1.25 to 29.15 µg/mL) in hospital effluent [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 The presence of such harmful pharmaceuticals badly affects plants and animals. 6 Removal of these drugs from wastewater over an extended period may result in the development of drug-resistant genes in living beings, which has detrimental impacts on the ecosystem. 7,8 Pharmaceutical drug residues and their many changed metabolites may result in a variety of adverse effects, including microorganism antibiotic resistance and chronic and acute toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is essential to deal with wastewater pollution caused by its excessive discharge. [2] Photocatalysis [3][4][5][6] is a new type of environmental treatment technology, which has the advantages of high efficiency, environmental protection, and low energy consumption, [7,8] and is widely used in water treatment, air purification, waste gas treatment, and other fields.…”
Section: Introductionmentioning
confidence: 99%